The Pragmatism at the Theme of Departure in ’Ferāqīyat Ibn Zuraīq Al-Baghdādī’ From Simile to Imagery - ALHARITHI, NAYEF BIN ABDULAZIZ BIN QALIL (Journal of Tikrit University for Humanities, 2024)
Modern critical theories are a lifesaver for literary texts and understanding them. Pragmatism is a literary philosophical doctrine that depends on truth after human experience. Ibn Zuraiq Al-Baghdadi, the well-known and unknown poet at the same time, made up a living text for us, in which the idea combines with the style and poetic images to introduce to us a living, speaking body that expresses us the suffering of estrangement and its conditions and horrors. This is what I will work to deduct from the orphan text, away from traditional studies that attempt to analyze the literary work according to classical tools. Therefore, this research will deal the idea of departure and estrangement from a linguistic perspective, in search of composition, poetic imagery, metaphorical values, and how to use images based on metaphors in an intense metaphorical way to reveal the emotional depth and spiritual dimension of the poet within a single poetic framework represented by the image belonging to his psychological world.